Expression of a Non-Traditional Chronotop in Lyrics - Khursanov Dilshod (Proceedings of The ICECRS, 2019)
The image in the poetry of the artistic space in a symbolic sense expresses the psychological state of the lyrical hero. These images have their exact and inaccurate features, and also relate to spaces that are only in the poet's mind, not related to an external object. The types of time change depending on the action of space. Stopped art forms of time are created.